Mast Cells, Cytokines and Asthma. Issue 2 (1994) - Redington, Anthony E; Howarth, Peter H
Abstract : The appreciation that asthma is a chronic inflammatory disorder of the airways has led to a reappraisal of the importance of different cell populations within the bronchial mucosa with respect to their role in the regulation of the cellular events in this disease. While mast cell degranulation has been implicated in the acute allergic bronchoconstrictor response, activation of this cell population has not been considered relevant to either the late phase inflammatory cell influx within the airways following allergen bronchoprovocation or to the mucosa! eosinophilia in chronic clinical disease. As such, attention has focused on the T lymphocyte as an orchestrator of these cellular events on account of its ability to synthesize and release cytokines relevant to the allergic process. It is now, however, realized that many cell populations within the airways are able to generate cytokines comparable with and complimentary to those produced by T lymphocytes and that asthma cannot be considered an inflammatory airway disorder dependent upon activation of one single cell population. This review details the current evidence that airway mast cells synthesize, store and release cytokines relevant to allergic inflammation and considers their potential involvement not only in the cellular influx within the airways but also in the fibrotic structural changes which are evident in chronic disease.